"Pierced finger ring": A rare case of a neglected burned hand. Issue 4 (June 2016) - Nascimento, Ricardo; Horta, Ricardo; Silva, Álvaro
Highlights: Chemical hand burns are very common and can lead to severe disability. Neglected burns in developing countries are rare compared to developing countries. Burn care education of the general population should be emphasized. Abstract: Neglected hand burns are common in developing countries but rare in developed countries due to easier access to healthcare. They can lead to severe deformities compromising hand function. The authors present an extreme case of a neglected chemical burn of the hand. The purpose of this article was to alert healthcare professionals and also the mass media to the need for burn care education of the general population.